Odnosi z zaposlenimi v storitvenem sektorju: interno komuniciranje, motiviranje, nagrajevanje in opolnomočenje kot predpogoji zadovoljstva zaposlenih in strank - Rijavec, Petja (Teorija in praksa, 1999)
Every organisation has an internal market which it must take care of. If this is done improperly, organisations activities which are oriented towards external publics will be endangered. Employee relations are a starting point of organisations management of external public relations. Employee relations are extremely important in the service sector. Service firms have, as opposed to industry sector, regular contacts with their customers. Key value of a service is produced in daily interactions between a contact person and a customer. This is the reason why employees (contact personnel) are becoming ambassadors of service organisations. The following text describes internal communications, motivation and empowerment as key tools of employee relations,key determinants of customer satisfaction and key determinants of quality in service sector.
Keywords: management; odnosi z javnostjo; zaposleni; storitvene dejavnosti; interno komuniciranje; poslovno komuniciranje; motiviranje